BENTUK DAN FUNGSI TEKS MANTRA - NFN Mulyanto; Edi Suwatno (Kadera Bahasa, 2017)
Mantra has a special form of language that is considered can connect people with things that are not concrete. The spelllanguage has poetic elements, such as rhyme and rhythm, and is considered to contain supernatural powers. The distinctivelanguage of the mantra needs to be studied in terms of form and function to be known by the people so that they will nothave wrong assumption on mantra. Data are obtained from various oral literary texts. This study uses the theory ofstructuralism of Jean Peager. The results show that the mantra language can be in the form of pantun, poetry, lyricprose, repetition of sound, and chant. Mantra has functions for kinship, treatment, pest eradication, immunity, games,health, love (compassion), and livelihood. AbstrakMantra memiliki bentuk bahasa khusus yang dianggap dapat menghubungkan manusia dengan halyang tidak konkret. Bahasa mantra berunsur puisi, seperti rima dan irama, dan dianggap mengandungkekuatan gaib. Bahasa yang khas pada mantra perlu dikaji bentuk dan fungsinya agar dapat diketahuioleh masyarakat sehingga mereka terhindar dari anggapan yang tidak benar terhadap mantra. Datadiperoleh dari berbagai teks sastra lisan. Penelitian ini menggunakan teori strukturalisme Jean Peager.Hasil penelitian menunjukkan bahwa bahasa mantra dapat berbentuk pantun, puisi, prosa lirik, pengulanganbunyi, dan kidung. Mantra memiliki fungsi untuk kekeluargaan, pengobatan, membasmi hama,kekebalan, permainan, kesehatan, cinta kasih (berkasih-kasihan), dan mata pencaharian.